An evidence‐based oral health promotion programme: Lessons from Leicester. (26th February 2018) - Murphy, JM; Burch, TE; Dickenson, AJ; Wong, J; Moore, R
Abstract : Objectives: To provide an overview and draw lessons from the establishment of a local oral health promotion programme for preschool children in Leicester, England (2013–2017). The article provides information on the strategic approach taken in Leicester, one of the most ethnically diverse cities in England, and also one of the most deprived. Over a third of children aged 3 years, and half of those aged 5 years, have experience of obvious dental decay. Methods: A description of the evolution and development of the programme is provided along with commentary by the authors. This includes the origins, design and evaluation of the programme. Results: Progress so far has been promising. There has been a statistically significant 8% decrease in the proportion of 5‐year‐old children in Leicester with dental decay from 2011/2012 to 2014/2015. This will need to be sustained and further developed to deliver the 10% reduction required within the strategy. Conclusions: The successful implementation of a local oral health improvement programme in Leicester has required leadership to coordinate a multiagency partnership approach to embedding effective concepts and realising opportunities collaboratively. However, longer term sustainability remains a concern.